2013
DOI: 10.1007/s00330-013-2768-3
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer recurrence after radical prostatectomy: the role of 3-T diffusion imaging in multi-parametric magnetic resonance imaging

Abstract: • Diffusion-weighted magnetic resonance imaging (DWI-MRI) is being increasingly used in oncology. • PSA analysis does not distinguish prostate cancer recurrence from distant metastasis. • DWI-MR can diagnose local prostate cancer recurrence after radical prostatectomy. • DWI-MR is almost comparable to DCE-MRI in detecting local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 29 publications
(38 reference statements)
3
98
1
6
Order By: Relevance
“…Recent literature on the topic shows that local recurrence was detected in larger series at a PSA level of around 0.8-1.3 ng/ml (45,46). Cirillo and coworkers estimated sensitivity of 84% and specificity of 89% in patients with a PSA level of ~1.2 ng/ml (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature on the topic shows that local recurrence was detected in larger series at a PSA level of around 0.8-1.3 ng/ml (45,46). Cirillo and coworkers estimated sensitivity of 84% and specificity of 89% in patients with a PSA level of ~1.2 ng/ml (35).…”
Section: Discussionmentioning
confidence: 99%
“…Cependant dans cette étude la dimension des récidives était supé-rieure à 1,5 cm pour un PSA de 1,23 ± 1,3 ng/mL. Dans une étude récente, Panebianco et al retrouvent une sensibilité et une spécificité de 98 % et 94 % pour la détection d'une récidive locale en associant la séquence morphologique et la séquence de perfusion pour une valeur de PSA moyen de 1,3 ng/mL (0,5-1,7 ng/mL) et une dimension moyenne de 5 ± 0,6 mm (4-8 mm) [7] Les séquences de diffusion sont également informatives, notamment avec l'utilisation de valeurs de b élevées à 3 T (supérieures à 1000 s/mm 2 et pouvant atteindre 3000 s/mm 2 ). Cependant elles sont souvent difficiles d'interprétation en raison d'artefacts dus aux mouvements digestifs [7].…”
Section: Aspect De La Récidive Séquences Fonctionnellesunclassified
“…43 Multiparametric imaging has well-recognized utility for microstructural and vascular tissue characterization and is rapidly establishing an expanding niche in the localization and management of prostate cancer. 44, 45 Yet, in general, it remains more difficult to assess metabolic activity with MRI than with PET; MR spectroscopy (MRS) is inconsistently used in clinics, as it requires significant expertise in acquisition and processing of the MR signal; whilst hyperpolarized (HP) MRI in addition requires significant investment in infrastructure. Studies validating the use of whole-body PET/MR compared with PET/CT have repeatedly shown increased sensitivity in early tumour detection, and using diffusion weighting on top of PET/MR can also detect treatment response at varying levels within metastases.…”
Section: 36mentioning
confidence: 99%